MicroRNA Profiling During Mulberry (Morus atropurpurea Roxb) Fruit Development and Regulatory Pathway of miR477 for Anthocyanin Accumulation - Dong, Xiaonan; Liu, Chaorui; Wang, Yuqi; Dong, Qing; Gai, Yingping; Ji, Xianling (Frontiers in Plant Science, 2021)
To understand the mechanism of miRNA-mediated development and ripening of mulberry fruits, three small RNA libraries from mulberry fruits at different development stages were constructed, and 159 conserved miRNAs as well as 86 novel miRNAs were successfully identified. Among the miRNAs identified, there were 90 miRNAs which showed different expression patterns at different stages of fruit development and ripening. The target genes of these differential expressed (DE) miRNAs were involved in growth and development, transcription and regulation of transcription, metabolic processes, and etc. Interestingly, it was found that the expression level of mul-miR477 was increased with fruit ripening, and it can target the antisense lncRNA (Mul-ABCB19AS) of the ATP binding cassette (ABC) transporter B 19 gene (Mul-ABCB19). Our results showed that mul-miR477 can repress the expression of Mul-ABCB19AS and increase the expression of Mul-ABCB19, and it acted as a positive regulator participating anthocyanin accumulation through the regulatory network of mul-miR477—Mul-ABCB19AS—Mul-ABCB19.